Educação infantil no campo um direito da criança na infância: avanços e retrocessos no município de Miracema - TO - Silva, Lucijane Ferreira da (Universidade Federal do Tocantins, 2019)
The objective of this work was to understand the reality experienced by children 's education students from the rural school in the Brejinho settlement in Miracema do Tocantins. The methodology was first used, the research in theoretical reference, where the theorists as: Miguel G. Arroyo (2011); Beatriz de Oliveira Abuchaim (2018); Fabiane Vanessa Breitenbach (2011) Roseli Salete Caldart (2012); Sônia Kramer (2003); Ana Paula Soares da Silva (2010), among others that were very important to support the preparation of this course completion work. Research was done on books, laws, decrees, articles in the areas of: Early Childhood Education, Field Education, Teacher Training, Scientific Research, theorists who could provide more background on the topic to be developed, as well as as a reference the PPP of the school and a field research, with the use of interviews the mothers of children of early childhood education. The development of the research made it possible to know the profile of the students of the Brejinho settlement, the pedagogical proposal for education in the field and finally the organization of the school's political and pedagogical project. It is concluded that to think about education in the field it becomes fundamental to know and understand the reality experienced in doing and being, integrating knowledge and forming participatory subjects capable of constructing their history. Therefore, there is a need to build the educational project of the school in a collective, contextualized and meaningful way, discussing and building a curriculum that meets the demands of the present and the future. The present reality has shown that there are structural and pedagogical difficulties that distance education from the countryside of the municipality to be and have a proposal of education of and in the field.